Islamic Religious Education Teachers' Problems In Implementing The Independent Curriculum At Min 15 Pidie Jaya - Yuliani Yuliani; Dhiauddin Dhiauddin; Saifuddin Saifuddin (Journal of Pedagogi, 2025)
The phenomenon of the independent curriculum problem at MIN 15 Pidie Jaya has experienced several changes, especially the learning system. The Independent Curriculum (Kurmer) gives religious teachers more freedom in choosing and deciding on different teaching tools according to the needs and interests of their students. Based on the research context above, the author conducted a study with the research title "Problems of Islamic Religious Education Teachers in Implementing the Independent Curriculum at MIN 15 Pidie Jaya". This type of research is qualitative. The method is descriptive. The formulation of the problem is how the problems of Islamic religious education teachers in implementing Kurmer at MIN 15 Pidie Jaya. The results of the study stated that there were three main problems in implementing Kurmer at MIN 15 Pidie Jaya for PAI teachers. First, the lack of teacher understanding due to minimal training. Second, difficulties in compiling teaching modules and learning objective flows, due to differences in the system with the previous curriculum. Third, challenges in differentiated learning, influenced by variations in student abilities, time constraints, and supporting facilities. Despite facing obstacles, PAI teachers try to overcome them through group learning strategies, collaboration in KKG, and support from the school. Ongoing support, such as intensive training, provision of adequate facilities, and access to relevant learning resources, is expected to increase the effectiveness of the implementation of Kurmer. Thus, the quality of PAI learning can be improved, while forming the character of students who are faithful, pious, and have noble character